From Benign To Malignant: A Case Report of Male Breast Cancer Mimicking Gynecomastia - Made Adwitya Krisna Kinasih; Ketut Suparna (Lembaga Pengembangan Kinerja Dosen, 2025)
Introduction: Carcinoma of the male breast is a very uncommon malignancy and accounts for less than 1% of all cases of breast carcinoma. The nonspecific presentation, along with low clinical suspicion, usually results in diagnosis at a delayed stage and poorer outcomes. Gynecomastia is a benign proliferation of male breast tissue and is the most common differential diagnosis that can mask underlying malignancy. Objective: To present a rare case of male breast cancer initially misdiagnosed as gynecomastia, and to emphasize the importance of early recognition and accurate differentiation between benign and malignant male breast conditions. Case Report: A 40-year-old male patient presented with a progressively enlarging right breast mass, which was earlier diagnosed as gynecomastia. The mass had been present since childhood but showed notable growth over the past two years. Physical examination revealed a hard, immobile, tender mass, 7 × 10 cm in size, without nipple discharge or axillary lymphadenopathy. Histopathology confirmed mixed carcinoma: invasive carcinoma of no special type with invasive lobular carcinoma. No metastasis was seen on imaging studies. Immunohistochemistry showed ER(+), PR(+), HER2(-), and Ki-67 at 20%. The patient underwent modified radical mastectomy, chemotherapy, and tamoxifen therapy, with no recurrence observed at six-month follow-up. Discussion: This case represents the diagnostic dilemma in differentiating male breast cancer from gynecomastia, particularly in young males without any risk factors. The diagnosis is even difficult when it is an invasive lobular carcinoma or a mixed type. Imaging and biopsy remain important in the management. Conclusion: Clinicians should have a high index of suspicion for malignancy when dealing with male breast masses. A timely diagnosis ensures appropriate treatment and results in better patient outcomes.